2023
DOI: 10.31234/osf.io/37m4q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do Meditation, Mindfulness, and Self-Compassion Impact Utilitarian Moral Judgment?

Abstract: Objectives: Meditation practices, mindfulness, and self-compassion have been found to impact our bodies and souls in many ways. However, can they also influence our morality, for example, what we think about right and wrong? We aimed to answer this question by focusing on utilitarian moral judgments. Methods: In Study 1, we measured participants’ frequency of meditation, their level of mindfulness, self-compassion, and their utilitarian moral judgment via two traditional moral dilemmas (switch and bridge) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…The results suggested that as the university classification improved, MI, psychological resources, and MP increased, while IA decreased. These findings align with previous research, indicating that sociodemographic factors, such as university classification, significantly affect the well-being of university students [8,15,69]. However, it is worth noting that the literature presents inconsistent findings, emphasizing the need for further research to gain a more comprehensive understanding of these relationships and differences.…”
Section: Discussionsupporting
confidence: 87%
“…The results suggested that as the university classification improved, MI, psychological resources, and MP increased, while IA decreased. These findings align with previous research, indicating that sociodemographic factors, such as university classification, significantly affect the well-being of university students [8,15,69]. However, it is worth noting that the literature presents inconsistent findings, emphasizing the need for further research to gain a more comprehensive understanding of these relationships and differences.…”
Section: Discussionsupporting
confidence: 87%